Cost‐effectiveness analysis of empagliflozin treatment in people with Type 2 diabetes and established cardiovascular disease in the EMPA‐REG OUTCOME trial1. Issue 11 (23rd July 2019) - Kansal, A.; Reifsnider, O. S.; Proskorovsky, I.; Zheng, Y.; Pfarr, E.; George, J. T.; Kandaswamy, P.; Ruffolo, A.
Abstract: Aim: In the EMPA‐REG OUTCOME trial, empagliflozin therapy reduced cardiovascular death by 38% compared with placebo when added to standard of care. Using the trial results, we created a discrete‐event simulation model to assess lifetime health economic outcomes in people with Type 2 diabetes and established cardiovascular disease. Methods: Time‐dependent survival regression analysis was performed on data from EMPA‐REG OUTCOME for 10 cardiovascular and renal events (e.g. stroke, heart failure hospitalization, macroalbuminuria, cardiovascular mortality) to capture event rates over time, and interaction between events. Model performance was assessed by comparing predicted and observed outcomes at 3 years. Costs in the United Kingdom (UK) and health utilities were obtained from published literature. Outcomes included cumulative event rates, life‐years, costs and quality‐adjusted life‐years (QALYs). Results: The model predicted an 18% relative increase (by 2.1 life‐years) in survival for empagliflozin (14.0 life‐years) vs. standard of care (11.9 life‐years), attributable to direct treatment effect on cardiovascular mortality, and to indirect effect via reductions in other events. Participants treated with empagliflozin may experience improved quality of life (1.0 QALY) and higher costs (£3737/participant), yielding an incremental cost‐effectiveness ratio (ICER) of £4083/QALY. Sensitivity analyses confirmed the robustness of these results to changes in input parameters. Conclusions: Based on extrapolation of EMPA‐REG OUTCOME trial data using a participant‐level simulation model, empagliflozin in addition to standard of care is projected to be highly cost‐effective using UK healthcare costs. The impact in other countries will vary due to differences in drug pricing and accrual of other costs. (Clinical Trial Registry No: NCT01131676) What's new?: The sodium–glucose co‐transporter 2 inhibitor empagliflozin has been shown to mitigate cardiovascular risk and cardiovascular death in people with Type 2 diabetes with established cardiovascular disease. An economic model was developed to extrapolate the outcomes of empagliflozin plus standard of care compared with standard of care alone over peoples' remaining lifetime in the United Kingdom. Patient‐level data from EMPA‐REG OUTCOME were analysed to generate time‐to‐event distributions for 10 cardiovascular and renal outcomes, including myocardial infarction, stroke, heart failure hospitalization, development of chronic kidney disease and cardiovascular mortality. Empagliflozin may have a positive benefit for people at costs acceptable to payers.